The Hoax Phenomenon in Indonesian Society: Observing Anti-Diversity Memes since 2014 - Aprinus Salam (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2018)
This article seeks to explain whether anti-diversity hoaxes that become viral on mass media disrupt the institutional memory of kebhinekaan (diversity) in Indonesian society. The spreading of hoaxes is a phenomenon of postmodern society, and thus this study uses a post-structural approach, in this case, using the theory of Slavoj Zizek. Memes used as data mostly deal with themes of nationality, ethnicity, and religion. The results of this study show that anti-diversity hoaxes are used for short-term purposes (power politics), so they do not intervene the institutional memory of Indonesian society and its belief in diversity.